Brain, behavior, and physiological changes associated with predator stress–An animal model for trauma exposure in adult and neonatal rats - Kigar, Stacey L.; Cuarenta, Amelia; Zuniga, Carla L.; Chang, Liza; Auger, Anthony P.; Bakshi, Vaishali P. (Frontiers in Molecular Neuroscience, 2024)
The use of predators and predator odor as stressors is an important and ecologically relevant model for studying the impact of behavioral responses to threat. Here we summarize neural substrates and behavioral changes in rats resulting from predator exposure. We briefly define the impact predator exposure has on neural targets throughout development (neonatal, juvenile, and adulthood). These findings allow us to conceptualize the impact of predator exposure in the brain, which in turn may have broader implications for human disorders such as PTSD. Importantly, inclusion of sex as a biological variable yields distinct results that may indicate neural substrates impacted by predator exposure differ based on sex.